Bardisms : Shakespeare for all occasions : wonderful words from the Bard on life's big moments (and some small ones, too) plus tips on how to use them in a toast, speech, or letter /: Shakespeare for all occasions : wonderful words from the Bard on life's big moments (and some small ones, too) plus tips on how to use them in a toast, speech, or letter. (©2009) - Unknown
No abstract available